EXPLORING TWITTER SENTIMENT: A MACHINE LEARNING APPROACH TO TWEET ANALYSIS (International Journal of Food and Nutritional Sciences, 2022)
This study presents a novel machine learning-based framework for the analysis of tweets, aimed at extracting meaningful insights from the vast and dynamic data generated on Twitter. With the exponential growth of social media, understanding public sentiment, trends, and topics of discussion has become increasingly vital for various applications, including marketing, political analysis, and public health monitoring. Our approach leverages advanced machine learning algorithms, including natural language processing (NLP) techniques, to classify and analyze tweet content effectively. By employing sentiment analysis, topic modeling, and user behavior analysis, the proposed framework enables the identification of prevailing sentiments and trends in real-time. The methodology utilizes a combination of supervised and unsupervised learning techniques, ensuring high accuracy in data classification while efficiently handling the unstructured nature of tweet data. Experimental results demonstrate the effectiveness of our approach, achieving significant improvements in sentiment classification accuracy compared to traditional methods. This research contributes to the field of social media analytics by providing a robust and scalable solution for understanding and interpreting Twitter data, ultimately facilitating informed decision-making across various sectors.